Hassan ibn Thabit and his poem praising his fellow tribesmen: A contribution to the study of spiritual culture of the Arab society in early Islamic times - D.Ye. Mishin (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper deals with the life and works of Hassan ibn Thabit (born around 562, died around 660), an Arabic poet. Particular attention has been paid to the poem praising his fellow tribesmen, which is found in some mediaeval sources. Hassan ibn Thabit came from the Khazraj tribe of Medina and in pre-Islamic times was mainly known as a poet who praised Arab Ghassanid kings of some parts of Syria. He embraced Islam early and became its ardent supporter. Hassan ibn Thabit did not participate in wars of the early Islamic times (although some mediaeval writers' assertions that this should be attributed to his cowardice do not appear well-founded) and defended Muslims and their doctrine in his poetry. According to a largely known story, in 630/31 he beat, in a poetic contest, one of the best poets of the Banoo Tameem tribe, which demonstrated the Muslims' virtues to the latter. As to the poem in question, it is composed in the traditional Arabic genre of praise to the poets' own tribe. Hassan Ibn Thabit credits his fellow tribesmen with virtues which a pre-Islamic poet would have mentioned too, but adds there to their positive response to Islam. The genre receives, thus, a new content, which is one of illustrations of how Islam took root in the Arabs' conscience in that time.